MicroRNAs in fruit trees: discovery, diversity and future research directions. (19th February 2014) - Solofoharivelo, M. C.; van der Walt, A. P.; Stephan, D.; Burger, J. T.; Murray, S. L.; Weber, A.
Abstract Since the first description of microRNAs (miRNAs) 20 years ago, the number of miRNAs identified in different eukaryotic organisms has exploded, largely due to the recent advances in DNA sequencing technologies. Functional studies, mostly from model species, have revealed that miRNAs are major post‐transcriptional regulators of gene expression in eukaryotes. In plants, they are implicated in fundamental biological processes, from plant development and morphogenesis, to regulation of plant pathogen and abiotic stress responses. Although a substantial number of miRNAs have been identified in fruit trees to date, their functions remain largely uncharacterised. The present review aims to summarise the progress made in miRNA research in fruit trees, focusing specifically on the economically important species Prunus persica, Malus domestica, Citrus spp, and Vitis vinifera. We also discuss future miRNA research prospects in these plants and highlight potential applications of miRNAs in the on‐going improvement of fruit trees.